Ekonomi Produsen dalam Perspektif Islam: Systematic Literature Review - Meirina Alkhoiriah Eka Putri; Retno Indri Yustika; Nia Andria Erzah; Eva Susanti; ⁠Novita Sari; Muhammad Yusup (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to formulate and synthesise the concepts, objectives, and characteristics of producer economics from an Islamic perspective through a Systematic Literature Review (SLR) approach. The background of this study stems from the dominance of conventional economic views that position producers as purely rational actors oriented towards profit maximisation, often overlooking dimensions of ethics, social justice, and moral responsibility. This study argues that Islamic economics offers an alternative paradigm in which production activities are regarded as value-driven endeavours directed not only towards material achievement but also spiritual fulfilment. Using the PRISMA protocol, the study systematically reviewed 65 scholarly articles published in reputable journals, which were subsequently analysed through thematic analysis and qualitative meta-synthesis. The findings indicate that Islamic producer economics emphasises a balance between material efficiency and spiritual accountability, grounded in Maqāṣid al-Sharīʿah, Islamic production ethics, tawhidic rationality, and social welfare orientation. Four major themes emerged from the literature: maqashid-based production, Islamic production ethics, tawhidic rationality, and social welfare orientation. This study concludes that Islamic producer economics constitutes a normative and holistic framework that rejects exploitative practices while integrating economic efficiency with moral and spiritual values, thereby providing a strong theoretical foundation for the development of empirical research and value-based production policies.